Sit or Squat? Toilet Type Is a Determinant of Diverticulosis Development - Buldukoğlu, Osman Çağın; Öcal, Serkan; Atar, Galip Egemen; Akbay Harmandar, Ferda; Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Diverticulosis coli is a common disorder of the colon, and a luminal pressure increase in the colon is a proposed mechanism in disease pathogenesis. Toilet types used around the world can be fundamentally categorized into 2 categories: sitting toilets and squatting toilets. Squatting toilets are shown to lead to better puborectalis muscle relaxation, wider anorectal angle, and require less straining compared to sitting toilets. Stemming from this knowledge, we hypothesized that toilet type would play a role in the complex pathogenesis of diverticulosis and that squatting toilets would lower the risk of diverticula formation. Materials and Methods: This study was conducted at Antalya Training and Research Hospital between January 2023 and July 2023. A 1-page questionnaire consisting of demographic data and bowel habits as well as diverticulosis-related parameters was prepared to gather the study data. Colonoscopy results were matched with corresponding questionnaires. Results: The study population consisted of 929 patients. Advanced age was found to be a risk factor for diverticulosis. Sitting toilet was also found to be a risk factor for diverticulosis in multivariate logistic regression analysis with an odds ratio of 3.36 (95% CI: 1.684-6.705) (P = .001). Conclusion: The results of this study revealed that toilet type is a determining factor in diverticulosis development, as was hypothesized during the conceptualization of the study. Revealing the potential contribution of the toilet type used to the development of a relatively common and impactful disorder like diverticulosis will lay the bedrock for future studies on the topic. Cite this article as: Buldukoğlu OÇ, Öcal S, Atar GE, Akbay Harmandar F, Çekin AH. Sit or squat? Toilet type is a determinant of diverticulosis development. Turk J Gastroenterol. 2024;35(6):475-480.